ANALISIS KESESUAIAN RENCANA PEMBANGUNAN HUTAN KOTA KAOMBONA BERDASARKAN PERATURAN MENTERI KEHUTANAN REPUBLIK INDONESIA - Ayub, Ayub; Hamzari, Hamzari; Ariyanti, Ariyanti (Jurnal Warta Rimba, 2020)
All the aforementioned areas must continue to be developed by the Regional Government (PEMDA) in each city in Indonesia in order to realize a green city because the LG is an institution responsible for providing and determining the function of a green space. This study aims to determine the suitability of the Kaombona urban forest development plan in Mantikulore District, Talise Village, Central Sulawesi Province with the applicable provisions based on the Regulation of the Minister of Forestry of the Republic of Indonesia Number: P.71 / Menhut-ii / 2009 concerning the implementation of urban forests. in March to May 2019, located in the City of Palu, Talise Village, Mantikulore District. The research location included the location of the City of Kaombona Forest. Data collection techniques are field observation, interviews and documentation. Later data were analyzed using the suitability of the Minister of Forestry Regulation of the Republic of Indonesia Number: P.71 / Menhut-II / 2009 and descriptive. The planning of the development of the Kaombona City forest is categorized according to the Minister of Forestry Regulation of the Republic of Indonesia No: P.17 / Menhut / -II / 2009 with 92% conformity rate. Kaombona City Forest is a type of recreation and protection City forest. The form of the Kaombona City Forest is in the form of clusters or groups with many strata. The function of the Kaombona City forest is the function of landscaping, environmental preservation and aesthetics.Keyword : the planning, development, city Forest.